The Relationship Of Human Resource Management Practices On Environmental Perfomance In Libya: The Mediating Role Of Organizational Culture - Hassan Saeid Ali Zidan
Contemporary firms are facing many pressures from stakeholders and shareholders to develop environmentally responsible activities. Environmental performance reflects an output demonstrating the degree to which firms are committed to protecting the natural environment. Environmental performance can be enhanced by greening the human resources management practices. The purpose of this study was to identify the effect of HRM practices on the environmental performance and to test the mediating effect of organizational culture between HRM practices and environmental performance. The data was collected from five manufacturing companies in Tripoli, Libya. A total of 309 employees have participated in this study. The preliminary analysis was conducted to prepare the data for further analysis. SPSS, as well as AMOS, were used to derive the findings of this study. The findings indicated that the effect of HRM practices on environmental performance is highly significant. The study also found that training, learning, and compensation are the most important variables in HRM practices. The effect of recruitment was found not significant. Moreover, the findings suggest that the HRM practices have a significant effect on organizational culture. In addition, organizational culture has a significant effect on the environmental performance. Organizational culture also played a partial mediating role between HRM practices and the environmental performance. Lastly, the variable of this study could explain almost half of the variation in the environmental performance. The findings in this study are significant and contribute to the theory, practice, and methodology of future research by extended the study on human resource management practices and environmental performance.